2018
DOI: 10.5194/acp-2018-359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wintertime photochemistry in Beijing: Observations of RO<sub>x</sub> radical concentrations in the North China Plain during the BEST-ONE campaign

Abstract: Abstract. The first wintertime in-situ measurements of hydroxyl (OH), hydroperoxy (HO 2 ) and organic peroxy (RO 2 ) 15 radicals (RO x =OH+HO 2 +RO 2 ) in combination with observations of total reactivity of OH radicals, k OH in Beijing are presented. The field campaign "Beijing winter finE particle STudy -Oxidation, Nucleation and light Extinctions" (BEST-ONE) was conducted at the suburban site Huairou near Beijing from January to March 2016. It aimed to understand oxidative capacity during wintertime and to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
60
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 38 publications
13
60
0
Order By: Relevance
“…OOA is also correlated with O x during daytime ( r 2 = 0.71 and 0.62), a tracer for the extent of photochemical processing in urban atmosphere (Herndon et al, ). Results here highlight the strong photochemical production of SOA in winter, consistent with a recent finding of high OH radical concentrations in winter in Beijing (Tan et al, ). In contrast, OPOA correlates the best with CO 2 + ( r 2 = 0.60–0.84), yet moderately correlates with O x during daytime ( r 2 = 0.44–0.69).…”
Section: Resultssupporting
confidence: 92%
“…OOA is also correlated with O x during daytime ( r 2 = 0.71 and 0.62), a tracer for the extent of photochemical processing in urban atmosphere (Herndon et al, ). Results here highlight the strong photochemical production of SOA in winter, consistent with a recent finding of high OH radical concentrations in winter in Beijing (Tan et al, ). In contrast, OPOA correlates the best with CO 2 + ( r 2 = 0.60–0.84), yet moderately correlates with O x during daytime ( r 2 = 0.44–0.69).…”
Section: Resultssupporting
confidence: 92%
“…concentrations measured during BEST-ONE (Tan et al, 2018) but these could not reproduce the OH 95 concentration observed when NO was above 1 ppbv or below 0.6 ppbv; consistent with previous campaigns when OH was measured and modelled under NO concentrations > 1 ppbv (Emmerson et al, 2005;Kanaya et al, 2007;Lu et al, 2013;Tan et al, 2017;Zhou et al, 2003). More recently, OH and HO2 were measured in central Beijing during winter-time at the Peking University (PKU) campus in November/December 2017 (Ma et al, 2019).…”
Section: Introduction 45supporting
confidence: 50%
“…During the photochemical cycle initiated by OH, NO can be oxidised to form NO2 via reaction with HO2 and organic peroxy radicals, RO2, and the subsequent photolysis of NO2 can lead to the net formation of ozone. It has been shown in previous field campaigns that measured mixing ratios of radicals have a strong dependence with j(O 1 D) (Ehhalt and Rohrer, 2000;Ma et al, 2019;Stone et al, 2012;Tan et al, 2018). Hence, the radical 65 concentrations measured during wintertime are typically expected to be lower than in the summertime due to lower photolysis rates of primary radical sources such as O3, HONO and HCHO.…”
Section: Introduction 45mentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information about the sampling site was described in Tan et al (2018). A weather station (Met one Instrument Inc., USA) was performed to measure meteorological parameters (ambient RH, temperature, wind speed, wind direction) and detailed aerosol particle physical and chemical properties were recorded using a suite of state-of-the-science instrumentation.…”
Section: Location and Instrumentationmentioning
confidence: 99%